Protective Effects of Necrostatin-1 in Acute Pancreatitis: Partial Involvement of Receptor Interacting Protein Kinase 1 - Yulin Ouyang; Li Wen; Jane A. Armstrong; Michael Chvanov; Diane Latawiec; Wenhao Cai; Mohammad Awais; Rajarshi Mukherjee; Wei Huang; Peter J. Gough; John Bertin; Alexei V. Tepikin; et al. (Cells, 2021)
Acute pancreatitis (AP) is a severe and potentially fatal disease caused predominantly by alcohol excess and gallstones, which lacks a specific therapy. The role of Receptor-Interacting Protein Kinase 1 (RIPK1), a key component of programmed necrosis (Necroptosis), is unclear in AP. We assessed the effects of RIPK1 inhibitor Necrostatin-1 (Nec-1) and RIPK1 modification (RIPK1K45A: kinase dead) in bile acid (TLCS-AP), alcoholic (FAEE-AP) and caerulein hyperstimulation (CER-AP) mouse models. Involvement of collateral Nec-1 target indoleamine 2,3-dioxygenase (IDO) was probed with the inhibitor Epacadostat (EPA). Effects of Nec-1 and RIPK1K45A were also compared on pancreatic acinar cell (PAC) fate in vitro and underlying mechanisms explored. Nec-1 markedly ameliorated histological and biochemical changes in all models. However, these were only partially reduced or unchanged in RIPK1K45A mice. Inhibition of IDO with EPA was protective in TLCS-AP. Both Nec-1 and RIPK1K45A modification inhibited TLCS- and FAEE-induced PAC necrosis in vitro. Nec-1 did not affect TLCS-induced Ca2+ entry in PACs, however, it inhibited an associated ROS elevation. The results demonstrate protective actions of Nec-1 in multiple models. However, RIPK1-dependent necroptosis only partially contributed to beneficial effects, and actions on targets such as IDO are likely to be important.